Neuraminidase Mediated Desialylation Augments AAV9 Mediated Gene Expression in Skeletal Muscle - Zhu, Hongling (J Gene Med, 2018)
BACKGROUND: Following systemic delivery, AAV9-mediated gene expression is significantly increased in ischemic versus non-ischemic muscle, suggesting AAV9 as an attractive vector for treating peripheral arterial disease (PAD). Potential mechanisms underlying ischemia-augmented expression include: 1) increased vascular permeability, and 2) “unmasking” of endogenous AAV9 receptors. Here, we endeavored to reconstitute the ischemic induction of AAV9 in vivo, using local injection of histamine (to increase vascular permeability) and neuraminidase (to desialylate cell surface glycans). METHODS: Bioassays were performed to optimize the effects of histamine and neuraminidase after intramuscular (IM) injection. Histamine and/or neuraminidase were then injected IM shortly before IV injection of an AAV9 vector expressing luciferase. Luciferase expression was serially assessed with bioluminescence imaging. At study’s end, tissues were harvested for assays of luciferase activity and AAV9 genome copy number to assess AAV-mediated gene expression and transduction, respectively. RESULTS: IM injection of either neuraminidase or neuraminidase plus histamine significantly increased both transduction and gene expression, whereas histamine alone had little effect. Pre-injection with neuraminidase increased AAV9-mediated gene delivery by 4–9 fold and luciferase activity by 60–100 fold. Luciferase activity in neuraminidase-injected muscle was >100-fold higher than in any off-target tissue (including heart, liver and brain). CONCLUSION: The ischemic induction of AAV9-mediated gene expression in muscle can largely be reconstituted by pre-injecting neuraminidase IM. This strategy may prove useful in future human gene therapy protocols as a quick and efficient means to selectively target systemically injected AAV9 to localized regions of muscle, thus decreasing the potential for adverse effects in off-target tissues.